2005
DOI: 10.1021/nl051781a
|View full text |Cite
|
Sign up to set email alerts
|

Resonant Tunneling in Nanocolumns Improved by Quantum Collimation

Abstract: We report on a quantum collimation effect based on surface depletion regions in AlAs/GaAs nanocolumns with an embedded resonant tunneling structure. The considered MBE-grown nanodevices have been fabricated by means of a top-down approach that employs a reproducible lithographic definition of the vertical nanocolumns. By analyzing the scaling properties of these nanodevices, we discuss how a collimation effect due to a saddle point in the confining potential can explain an improved device performance of the ul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
2

Year Published

2006
2006
2010
2010

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 26 publications
1
39
2
Order By: Relevance
“…A typical "top-down" approach to the fabrication of epitaxial quasi-1D nanostructures would utilize nano-lithographic techniques, such as electron beam lithography (EBL) and proximal probe patterning, in combination with dry-etching methods to remove excess material from planar epitaxial structures (Wensorra et al, 2005). However, top-down methods do not warrant a sufficiently low dimensionality, the spatial resolution limit of nano-lithographic techniques being typically above the size (20 nm) below which quantumconfinement effects appear in these nanostructures.…”
Section: "Top-down" Versus "Bottom-up" Technologies For Iii-v Nanowirmentioning
confidence: 99%
See 1 more Smart Citation
“…A typical "top-down" approach to the fabrication of epitaxial quasi-1D nanostructures would utilize nano-lithographic techniques, such as electron beam lithography (EBL) and proximal probe patterning, in combination with dry-etching methods to remove excess material from planar epitaxial structures (Wensorra et al, 2005). However, top-down methods do not warrant a sufficiently low dimensionality, the spatial resolution limit of nano-lithographic techniques being typically above the size (20 nm) below which quantumconfinement effects appear in these nanostructures.…”
Section: "Top-down" Versus "Bottom-up" Technologies For Iii-v Nanowirmentioning
confidence: 99%
“…Free-standing nanowires based on III-V compound semiconductors are nowadays in the focus of intense research activities throughout the world; this in reason of the prominent role of these compounds in the optoelectronic arena. Demonstration of resonant tunnelling diodes (Bjork et al 2002;Wensorra et al, 2005), single electron transistors (Thelander et al, 2003;Thelander et al, 2005), and photodetectors (Pettersson et al, 2006) based on quasi-1D nanostructures of III-V compounds have been reported. Also intense single photon sources have been fabricated by embedding InGaP quantum dots in free-standing GaP nanowires (Borgström et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Both systems are also strongly related to more fundamental research structures developed in the last years, like in-plane-gate transistors [6], single-electron transistors [7], silicon-on-insulator planar double-gate transistors [8], non-planar double-gate FinFETs [9], non-planar trigate transistors [10], nanowire-based fieldeffect transistors (FET) [11], nanowire resonant tunneling diodes [12,13], nanowire lasers [14], or nanowire qubits [15], whose maturity has still to be proven for industrial applications. Their structural complexity has also progressively increased, allowing for double-barrier structures [12,13], or multiple core-shell layers [14,16]. The material composition includes mainly III-V materials GaAs/AlGasAs [6,7,13], InAs/InP [12], GaN/InGaN [14], but also group IV materials Si [4,17], and Si/Ge [11,15], predominant in the industry.…”
Section: Introductionmentioning
confidence: 99%
“…Their structural complexity has also progressively increased, allowing for double-barrier structures [12,13], or multiple core-shell layers [14,16]. The material composition includes mainly III-V materials GaAs/AlGasAs [6,7,13], InAs/InP [12], GaN/InGaN [14], but also group IV materials Si [4,17], and Si/Ge [11,15], predominant in the industry.…”
Section: Introductionmentioning
confidence: 99%
“…As a prototype system, one-dimensional nanowire-based structures [3][4][5] have recently attracted great interest due to their advantageous electrostatics and transport properties. [6][7][8] From a different perspective, they also represent model systems for the study of technological as well as physical challenges in future nanodevice designs.…”
Section: Introductionmentioning
confidence: 99%